Tracking the past: Interspersed repeats in an extinct Afrotherian mammal, Mammuthus primigenius - Zhao, Fangqing; Qi, Ji; Schuster, Stephan C. (Genome Research, 2009)
The woolly mammoth (Mammuthus primigenius) died out about several thousand years ago, yet recent paleogenomic studies have successfully recovered genetic information from both the mitochondrial and nuclear genomes of this extinct species. Mammoths belong to Afrotheria, a group of mammals exhibiting extreme morphological diversity and large genome sizes. In this study, we found that the mammoth genome contains a larger proportion of interspersed repeats than any other mammalian genome reported so far, in which the proliferation of the RTE family of retrotransposons (covering 12% of the genome) may be the main reason for an increased genome size. Phylogenetic analysis showed that RTEs in mammoth are closely related to the family BovB/RTE. The incongruence of the reconstructed RTE phylogeny indicates that RTEs in mammoth may be acquired through an ancient lateral gene transfer event. A recent proliferation of SINEs was also found in the probocidean lineage, whereas the Afrotherian-wide SINEs in mammoth have undergone a rather flat and stepwise expansion. Comparisons of the transposable elements (TEs) between mammoth and other mammals may shed light on the evolutionary history of TEs in various mammalian lineages.